Job Satisfaction in The Light of Some Variables (Field Study on a Sample of Faculty Members at Tishreen University) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The purpose of this study was to determine the level of job satisfaction among faculty members at Tishreen University, as well as the differences in their job satisfaction according to the variables: gender, academic qualification, job rank, college and years of experience.To achieve these goals, the researcher used the measure of job satisfaction (prepared) which consists of (52) items divided into eight dimensions.The study was applied to a sample of the faculty members whose number was (86) chosen from an original community composed of all the faculty members of Tishreen University, which number (1155) members for the academic year 2017/2018.The study showed the following results: the level of job satisfaction among Tishreen faculty members is low. There are no differences in job satisfaction among faculty members according to gender, academic qualification, job rank, college and years of experience. While there were differences in job satisfaction among faculty members in theoretical and applied colleges on the dimension of satisfaction of needs and scientific research in favor of applied colleges.